Writing Competence of First Year College Students at a State University - Salvador, Juvelyn (JPAIR Multidisciplinary Research, 2024)
Writing is an essential skill for students doing many academic writing assignments. However, despite educational efforts to develop this skill, many still struggle for diverse reasons. This study determines the writing competence of first-year Bachelor of Elementary Education, Bachelor of Technical Vocational Education, and Bachelor of Science in Agriculture college students at Catanduanes State University, Panganiban Campus. It offers teaching or curricular strategies to improve writing interest. This utilized descriptive correlational research from 157 respondents derived through fishbowl sampling. The findings revealed that the majority of respondent’s parents were high school graduates. They are "often" exposed to broadcast media (movies, MP3, TV, internet) and "seldom" read print media (news, novels, commentaries, essays). They are "highly motivated" to learn from references and read stories while "slightly motivated" with book gifts and quizzes after reading. When correlated with Pearson chi-square, these two variables disclosed no significant relationship. Thus, a pressing need to analyze the gap and resolve writing difficulties aligned with Flower and Hayes’ Cognitive Process Writing Theory. Basic writing workshops, online webinars, and instructional material development on improving writing competence are research outputs to orchestrate the best writing techniques to improve writing competence.